BUILDING INDICATORS OF COMMUNITY RESILIENCE TO DISASTERS IN BRAZIL: A PARTICIPATORY APPROACH - CICCOTTI,LARISSA (2020)
Abstract Community resilience is essential for disaster management and its measurement is necessary to support decision-making. This paper presents as first list of community resilience indicators for Brazilian municipalities, resulting from literature review, experts’ consulting and application of the Delphi method. The experts group consisted of public managers (43%) and researchers (57%). The study comprised six phases: conceptual framework selection; composition of the indicators list; elaboration of evaluation tool (Delphi method); selection and invitation to experts; evaluation of indicators; and data analysis. As a result, the importance of 101 indicators distributed in six dimensions (environmental; social; economic; institutional; infrastructure; social capital) achieved consensus among the experts after two rounds. In the first round, 98 indicators were submitted to the evaluation of 97 specialists, with the possibility of proposing new indicators, while in the second round the final list reached consensus among the 72 respondents. The Institutional and Infrastructure dimensions were predominant, evidencing the value of public policies and urban infrastructure for community resilience to disasters in the perception of Brazilian experts.